PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP KETEPATAN WAKTU DENGAN REPUTASI KANTOR AKUNTAN PUBLIK SEBAGAI PEMODERASI - Devi, Ni Luh Lemi Sushmita; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2016)
The purpose of this research is to determine effect of profitability and solvency, individually, to on timeliness of submission of financial report, and to determine capable or not reputation or KAP moderate profitability and solvency, individually, on timeliness of submission of financial report. This research was carried out atbanking companies listed in Indonesian Stock Exchange. This research used purposive sampling technique. Number of samples used as many as 28 companies with 140 of observation samples. The analytical instrument used is MRA. Based on this research result, profitability and solvency, individually, did not effect to timeliness of submission of financial report. Reputation of KAP be able to strengthen effect of profitability on submission of timeliness of financial report, but weaken effect of solvency on submission of timeliness of financial report.
Keywords: profitability; solvency; reputation of KAP; timeliness